Mechanical removal of senescent material for pasture recovery - Villalobos-Villalobos, Luis A. (2019)
Introduction. The accumulation of senescent material in tropical pastures is the result of high biomass production and low level of utilization. By removing senescence pastures, cattle can graze at lower levels, allowing regrowth with higher nutrient content. Objective. The objective of this study was to evaluate the response of African stargrass (Cynodon nlemfuensis Vanderyst.) and Mombasa (Megathyrsus maximus Jacq.) to removal of senescent material based on its structural components, biomass and nutrient content. Materials and methods. This experiment was carried out between April to August 2017 in two farms, one located in Turrialba, Cartago, and the other in San Carlos, Alajuela. A chi-squared design was used to evaluate the removal of senescent material versus the respective controls. Results. Senescence grass removal increased the proportion of leaves in both kinds of grasses. Yielded biomass in senescence material removal plots had higher protein and lower cell wall content, producing more digestible forage. The structural changes had a longer duration in the Mombasa grass, which was attributed to the diffrerences in plant architecture with respect to the Star grass. Conclusion. Removing senescent material from tropical pastures is a strategy to modify the structure and enhance the nutritional value of dry matter yield. Both the type of system and grazing intensity may contribute to reducing senescence accumulation, increasing the nutritive value of forages in the long term.